Resource discovery and scalability-aware routing in cloud federation using distributed meta-brokering paradigm. (25th October 2021) - Latif, Sajid; Humayun, Mamoona; Sharif, Abida; Kadry, Seifedine
Resource management in large-scale distributed systems is comprised of key factors e.g. scheduling, monitoring and discovery of potential resources. Due to highly dynamicity and heterogeneity, effective management of distributed resources is a challenging task. Resource discovery is a complex process to find the optimal resources for efficient allocation. Interconnected cloud is the emerging variant of large-scale distributed computing to cover the extensive footprint. In this study, meta-brokering driven distributed discovery approach is proposed for optimal applications execution. Queries get propagated with minimal routing cost in meta-brokering P2P instance overlay while maintaining the ontological information. Uniform configuration of instances enables the distributed brokerage and ontologies realise the interoperability. Moreover, distributed instances are resilient as contrary to centralised counterparts. This decoupled paradigm enables the discovery with fine-grained management through distinct modules while complementing the scalability factor.